Effect of crew resource management on diabetes care and patient outcomes in an inner-city primary care clinic. Issue 4 (12th August 2007) - Taylor, Cathy R; Hepworth, Joseph T; Buerhaus, Peter I; Dittus, Robert; Speroff, Theodore
Abstract : Background: Diabetes care in our inner-city primary care clinic was suboptimal, despite provider education and performance feedback targeting improved adherence to evidence-based clinical guidelines. A crew resource management (CRM) intervention (communication and teamwork, process and workflow organisation, and standardised information debriefings) was implemented to improve diabetes care and patient outcomes. Objective: To assess the effect of the CRM intervention on adherence to evidence-based diabetes care standards, work processes, standardised clinical communication and patient outcomes. Methods: Time-series analysis was used to assess the effect on the delivery of standard diabetes services and patient outcomes among medically indigent adults (n = 619). Results: The CRM principles were translated into useful process redesign and standardised care approaches. Significant improvements in microalbumin testing and associated patient outcome measures were attributed to the intervention. Conclusions: The CRM approach provided tools for management that, in the short term, enabled reorganisation and prevention of service omissions and, in the long term, can produce change in the organisational culture for continuous improvement.